A 2.5-D frequency-domain nonlinear computer model of coupled-cavity traveling wave tubes. Issue 5 (19th August 2014) - Bai, Chunjiang; Hu, Yulu; Li, Jianqing; Sykulski, Jan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The paper aims to present a 2.5-dimensional (2.5-D) frequency-domain nonlinear computer model for the beam-wave interaction of coupled-cavity traveling wave tubes (CC-TWTs). Design/methodology/approach MKK (proposed by Malykhin, Konnov, and Komarov) equivalent circuit model is used to describe the coupled-cavity slow-wave structure. And the losses are taken into account in the MKK equivalent circuit. Instead of one-dimensional (1-D) disk model, the electron beam is divided into a set of discrete rays and the electron dynamics are treated using the three-dimensional (3-D) Lorentz force equations. Findings The simulated result obtained show that the computer model can give a good predict for coupled-cavity traveling wave tubes in V-band. Practical implications The computer model is capable of treating nonlinear problems. Compared with particle-in-cell (PIC) simulation, the 2.5-D frequency-domain computer model spends less time. Besides, the 3-D electron trajectory can be used to design high-efficiency collectors for coupled-cavity traveling wave tubes. Originality/value The computer model is able to simulate nonlinear problems of coupled-cavity TWT faster.